IL-22 Paucity in APECED Is Associated With Mucosal and Microbial Alterations in Oral Cavity - Kaleviste, Epp; Rühlemann, Malte; Kärner, Jaanika; Haljasmägi, Liis; Tserel, Liina; Org, Elin; Trebušak Podkrajšek, Katarina; Battelino, Tadej; Bang, Corinna; Franke, Andre; Peterson, Pärt; Kisand, Kai (Frontiers in Immunology, 2020)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is caused by recessive mutations in the AIRE gene. The hallmark of the disease is the production of highly neutralizing autoantibodies against type I interferons and IL-22. Considering the importance of IL-22 in maintaining mucosal barrier integrity and shaping its microbial community, we sought to study potential changes in the oral cavity in this model of human IL-22 paucity. We found that besides known Th22 cell deficiency, APECED patients have significantly fewer circulating MAIT cells with potential IL-22 secreting capacity. Saliva samples from APECED patients revealed local inflammation, the presence of autoantibodies against IFN-α and IL-22, and alterations in the oral microbiota. Moreover, gene expression data of buccal biopsy samples suggested impaired antimicrobial response and cell proliferation, both of which are processes regulated by IL-22. Our data complement the knowledge gained from mouse models and support the concept of IL-22 being a critical homeostatic cytokine in human mucosal sites.